Phenotypic evaluation of gamma-induced dwarf mutants in Dendrobium crumenatum at M2 generation - DWIYANI, RINDANG; DARMAWATI, IDA AYU PUTRI; KAWURI, RETNO; FITRIANI, YUYUN; KAMUHI, RINI HERMINA; HANIFAH, WAFA’ NUR; SANTIKA, I PUTU BENNY (Asian Journal of Agriculture, 2026)
Abstract. Dwiyani R, Darmawati IAP, Kawuri R, Fitriani Y, Kamuhi RH, Hanifah WN, Santika IPB. 2026. Phenotypic evaluation of gamma-induced dwarf mutants in Dendrobium crumenatum at M2 generation. Asian J Agric 10 (1): g100150. https://doi.org/10.13057/asianjagric/g100150. Bali, Indonesia, has strong potential for the development of ornamental orchids, particularly compact cultivars with high commercial value. Dendrobium crumenatum, a native Indonesian orchid, is widely appreciated for its white, fragrant flowers; however, its tall growth habit limits its suitability as a potted ornamental plant. This study aimed to induce and evaluate dwarf phenotypes in D. crumenatum using gamma irradiation. Plantlets were exposed to 0, 5, 10, 15, and 20 Gy, arranged in a completely randomized design with five replicates and three plantlets per replicate (n=75). Morphological traits were assessed after in vitro culture and acclimatization. Data were analyzed using analysis of variance followed by the Least Significant Difference (LSD) test at a 5% significance level (p
Keywords: Dendrobium crumenatum, gamma irradiation, mutation breeding, ornamental orchid